News on Corruption in the Wall Street Journal and the Corruption Perception Index (CPI) - Jing, Runtian; Zhang, Gaoliang; Feng, Tianli (Journal of Comparative International Management)

(untitled) (Management Futures, 2006)
Based on cross-time-section series data collected from Wall Street Journal (WSJ), this article suggests that the Corruption Perceptions Index (CPI) for 60 countries/regions published by Transparency International is highly correlated with WSJ news about “corruption”, especially for eight strong countries. Compared to a slight converging trend of CPI standard deviation, the CPI score presents no significant response to time. Our partial multiple correlation model suggests that WSJ news may be a good indicator of corruption levels in a country, although not as a potential cause influencing CPI.